The conservation of a 19th century framed miniature portrait painted on ivory - Violeta Machado Prin (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article addresses the conservation treatment of a 19th century framed miniatured portrait painted on ivory. The object was in poor condition, with all the pieces necessary to hold the object separated and with the attempt of securing these parts with brown and clear adhesive tape. This article addresses the condition of the object and consequently, the treatments undertaken for its conservation: tape removal procedure with heat and solvents; paper mending and repairs; cleaning process of the back of the painting and remounting process of the frame with appropriate conservation materials to strengthen it and provide stability.